Analisis Strategi Pemasaran Perusahaan Sekuritas Untuk Menarik Minat Masyarakat dalam Berinvestasi (Studi Kasus PT. Korea Investment and Sekuritas Indonesia (KISI)) - Meilinda Ritonga; Ibnu Syawali Manurung; Jelita Handayani Rambe; Muhammad Ikhsan Harahap (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this writing is to find out what strategies are used by KISI companies in attracting people to invest in their companies. The research method used is qualitative descriptive which aims to describe the marketing strategy carried out by securities companies to attract public interest in investing in PT. Korea Investment and Sekuritas Indonesia (KISI) with literature studies or literature reviews and interviews as the source of this research data. The result of this writing is that KISI uses differentiation strategies and marketing mix to promote their company